Heterogeneous recessions and expansions in Mexican regions and sectors - Miguel A. Mascarúa Lara (Banco de México, 2024)
This study uses a Markov regime-switching model with time-varying means to identify subnational, sectoral, and national economic phases. The model replicates the official business cycle dates in Mexico and quantifies the contributions of states, regions, and sectors to the national recession probability. The findings show that the southern region contributes differently to the national recession probability than the other regions, even increasing it during expansionary periods at the national level. Additionally, the manufacturing sector is found to account for up to half of the national recession probability.
Keywords: C22; E32; E27; 330; Business cycles; Expansions; Recessions